The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1021/jp810878y
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylated Carbon Nanotubes under External Electrical Field: An Ab Initio Investigation

Abstract: Carboxylated semiconductor and metallic carbon nanotubes under transverse electrical fields are investigated through density functional theory based on first-principles calculations. The external field polarizes the system, resulting in an induced electric dipole moment toward the incident field with the modulus directly dependent on the field strength. The structural and electronic properties of the resulting system due to the orbital hybridization between the nanotube and COOH states are shown to be affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…). The following is found: p=αE+β, where p is the module of the electric dipole moments, E is the applied electric field, α represents the electric susceptibility , and β the electric dipole moment in the absence of an electric field. For pristine and functionalized CCN with carboxyl, amine, amide, or hydroxyl groups Eq.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…). The following is found: p=αE+β, where p is the module of the electric dipole moments, E is the applied electric field, α represents the electric susceptibility , and β the electric dipole moment in the absence of an electric field. For pristine and functionalized CCN with carboxyl, amine, amide, or hydroxyl groups Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical functionalization of nanotubes can also facilitate their interactions with other chemical groups . Nevertheless, studies have reported that there are other ways to change electronically the nanotubes properties . One of them, studied here, is the application of electric fields that can polarize the system, resulting in an induced dipolar momentum of the tube in the incident field direction .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many density functional theory (DFT) calculations have been conducted on covalently functionalized CNTs in order to determine the influence of grafted organic groups on the electronic structure of CNTs, [46][47][48][49] to the best of our knowledge no mechanistic studies of the formation of these functional groups on CNT surface have been undertaken. Such multistep mechanistic studies are usually limited to the preliminary interaction between CNTs surfaces and atomic oxygen [50][51][52] or NO 2 + ions.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] Ab initio calculations indicate that the longitudinal polarizability is roughly proportional to its length and that the presence of functional groups on CNTs does not alter the polarization characteristics significantly. 34 Due to the myriad applications of aligned CNT deposits on substrates, the process of alignment of CNTs in presence of applied electric field has recently generated great interest in the scientific community. Overall, under an applied electric field, charged CNTs experience two types of motion: electrophoretic rotation followed by electrophoretic migration leading to deposition.…”
Section: Introductionmentioning
confidence: 99%